VGLUTs and glutamate synthesis-focus on DRG neurons and pain - Malet, Mariana (2015)
The amino acid glutamate is the principal excitatory transmitter in the nervous system, including in sensory neurons that convey pain sensation from the periphery to the brain. It is now well established that a family of membrane proteins, termed vesicular glutamate transporters (VGLUTs), serve a critical function in these neurons: they incorporate glutamate into synaptic vesicles. VGLUTs have a central role both under normal neurotransmission and pathological conditions, such as neuropathic or inflammatory pain. In the present short review, we will address VGLUTs in the context of primary afferent neurons. We will focus on the role of VGLUTs in pain triggered by noxious stimuli, peripheral nerve injury, and tissue inflammation, as mostly explored in transgenic mice. The possible interplay between glutamate biosynthesis and VGLUT-dependent packaging in synaptic vesicles, and its potential impact in various pain states will be presented.